Comparative analysis of outcome measures used in examining neurodevelopmental effects of early childhood anesthesia exposure - Ing, C.; Dimaggio, C.; Malacova, Eva; Whitehouse, A.; Hegarty, M.; Feng, T.; Brady, J.; Von Ungern-Sternberg, B.; Davidson, A.; Wall, M.; Wood, A.; Li, G.; et al. (Lippincott Williams and Wilkins, 2014)
INTRODUCTION:: Immature animals exposed to anesthesia display apoptotic neurodegeneration and neurobehavioral deficits. The safety of anesthetic agents in children has been evaluated using a variety of neurodevelopmental outcome measures with varied results. METHODS:: The authors used data from the Western Australian Pregnancy Cohort (Raine) Study to examine the association between exposure to anesthesia in children younger than 3 yr of age and three types of outcomes at age of 10 yr: neuropsychological testing, International Classification of Diseases, 9th Revision, Clinical Modification-coded clinical disorders, and academic achievement. The authors' primary analysis was restricted to children with data for all outcomes and covariates from the total cohort of 2,868 children born from 1989 to 1992. The authors used a modified multivariable Poisson regression model to determine the adjusted association of anesthesia exposure with outcomes. RESULTS:: Of 781 children studied, 112 had anesthesia exposure. The incidence of deficit ranged from 5.1 to 7.8% in neuropsychological tests, 14.6 to 29.5% in International Classification of Diseases, 9th Revision, Clinical Modification-coded outcomes, and 4.2 to 11.8% in academic achievement tests. Compared with unexposed peers, exposed children had an increased risk of deficit in neuropsychological language assessments (Clinical Evaluation of Language Fundamentals Total Score: adjusted risk ratio, 2.47; 95% CI, 1.41 to 4.33, Clinical Evaluation of Language Fundamentals Receptive Language Score: adjusted risk ratio, 2.23; 95% CI, 1.19 to 4.18, and Clinical Evaluation of Language Fundamentals Expressive Language Score: adjusted risk ratio, 2.00; 95% CI, 1.08 to 3.68) and International Classification of Diseases, 9th Revision, Clinical Modification-coded language and cognitive disorders (adjusted risk ratio, 1.57; 95% CI, 1.18 to 2.10), but not academic achievement scores. CONCLUSIONS:: When assessing cognition in children with early exposure to anesthesia, the results may depend on the outcome measure used. Neuropsychological and International Classification of Diseases, 9th Revision, Clinical Modification-coded clinical outcomes showed an increased risk of deficit in exposed children compared with that in unexposed children, whereas academic achievement scores did not. This may explain some of the variation in the literature and underscores the importance of the outcome measures when interpreting studies of cognitive function. © 2014 The American Society of Anesthesiologists, Inc.